(untitled) (Applied Biological Research, 2012)
The effect of UV-β radiations on some growth and biochemical parameters of aquatic fern Azolla filiculoides was assessed for induced instability in the fern. UV-β radiation @ 6.8 Wm-2 was made incident on the fronds of fern for various periods (20, 40 and 60 min). Plants exhibited mild to severe injury symptoms and the extent of injury was estimated by observing the visiblesymptoms of chlorosis and necrosis. Fern biomass, doubling time, average root number and average root length was also measured. Severe chlorotic injury followed by necrosis occurred in the plants exposed to UV-β radiations for 60 min. With increase in exposure time to UV-β radiation the fern biomass, average root number and average root length weresignificantly reduced with associated increase in doubling time. 5-amino laevulinic acid (the precursor of chlorophyll) content of A. filiculoides was severely reduced in all exposure periods resulting in less chlorophyll biosynthesis by plant. The carotenoid content increased at no or mild injury but decreased due to severe injury. Starch, sugar and protein contents showed decreasing trend with increase in exposure time. Preliminary observations indicated that the disturbances in photosynthetic machinery lead to decrease in biomass production revealing physiological stress on A. filiculoides due to UV-β radiations.